KONSEP HOMINISASI DAN HUMANISASI MENURUT DRIYARKARA - Asep Rifqi Abdul Aziz (UIN Raden Mas Said Surakarta, 2016)
Changing of epoch with all brought payload is truly inevitable. Progress will continue to walk along with the growth of the human being’s intelligence. The rapid of the globalization today is likely giving more problems faced by human being. Indeed, globalization does not fully bring negative effect, as long as human beings are able to utilize its product wisely, including in the educational sectors. This article tries to offer an alternative perspective on how to overcome the various problems in the life of society nowadays; i.e. through the idea of Driyarkara, on hominization and humanization: an educational philosophy to promote human’s awareness to humanize human being.